Biogas-pH automation control strategy for optimizing organic loading rate of anaerobic membrane bioreactor treating high COD wastewater. (March 2016) - Yu, Dawei; Liu, Jibao; Sui, Qianwen; Wei, Yuansong
Graphical abstract: Highlights: Novel control strategy doubled OLR of AnMBR treating high COD wastewater. COD removal rate achieved 99.1% allow for efficient and compacted digestion. Gas-liquor two phase monitoring sensitively reflected digestion status. Dynamic kinetic and pH titration determined exact threshold for control object. The novel strategy seized CO2 for ternary buffer system and maintained pH > 7.4. Abstract: Control of organic loading rate (OLR) is essential for anaerobic digestion treating high COD wastewater, which would cause operation failure by overload or less efficiency by underload. A novel biogas-pH automation control strategy using the combined gas-liquor phase monitoring was developed for an anaerobic membrane bioreactor (AnMBR) treating high COD (27.53 g·L −1 ) starch wastewater. The biogas-pH strategy was proceeded with threshold between biogas production rate >98 Nml·h −1 preventing overload and pH > 7.4 preventing underload, which were determined by methane production kinetics and pH titration of methanogenesis slurry, respectively. The OLR and the effluent COD were doubled as 11.81 kgCOD·kgVSS −1 ·d −1 and halved as 253.4 mg·L −1, respectively, comparing with a constant OLR control strategy. Meanwhile COD removal rate, biogas yield and methane concentration were synchronously improved to 99.1%, 312 Nml·gCODin −1 and 74%, respectively. Using the biogas-pH strategy, AnMBR formed a "pH self-regulation ternary buffer system" which seizes carbon dioxide and hence provides sufficient buffering capacity.